Desain Instrumen Tes Pemahaman Konsep Berbasis HOT dengan Analisis Model Rasch - Aprilia, Nurkintan; Susilaningsih, Endang; Priatmoko, Sigit; Kasmui, Kasmui (Universitas Negeri Semarang, 2020)
The demands of the 21st century, students must have a high understanding of concepts. This study aims to develop a HOT-based two-tier multiple choice diagnostic test instrument to determine the profile of students' understanding of concepts analyzed using the Rasch model. The research method used is research and development. The design of this study uses the 4D model. The subjects in this study were students of class X SMAN 1 Bae Kudus. Data collection techniques are done by observation, documentation, tests, and questionnaires. Data analysis uses classical model analysis and Rasch model. In the classical model analysis, analysis of validity, reliability, difference power, and item difficulty level was carried out, while the Rasch model analysis carried out reliability analysis, item fit, wright map, item measure, person fit, person measure and DIF items. The test instrument in this study tested the reliability and validity of the contents, constructs and items. Profile understanding of students' concepts with the criteria of understanding concepts by 55%, positive misconceptions by 10%, negative misconceptions by 17%, and not understanding concepts by 18%. Both students and teachers gave positive responses to test instrument. As many as 97% of students gave positive responses to the developed test instruments.